2015
DOI: 10.1007/s10552-015-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in breast cancer survival in New Zealand: contributions of differences in screening, treatment, tumor biology, demographics and comorbidities

Abstract: Māori women experience an age-adjusted risk of death from breast cancer, which is more than twice that for NZ European women. Equity-focussed improvements in health care, including increasing mammographic screening coverage and providing equitable quality and timely cancer care, may improve the survival disparity between Māori and NZ European women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…In New Zealand, differences have been shown in the presentation and outcomes of breast cancer for Māori and Pacific women compared with NZ Europeans [6,7]. A prior study using NZ cancer registry data did not show differences in breast cancer mortality or stage of diagnosis for urban versus rural women after adjustment for age, ethnicity and socioeconomic status [8].…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, differences have been shown in the presentation and outcomes of breast cancer for Māori and Pacific women compared with NZ Europeans [6,7]. A prior study using NZ cancer registry data did not show differences in breast cancer mortality or stage of diagnosis for urban versus rural women after adjustment for age, ethnicity and socioeconomic status [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our own work using the NZ Waikato Breast Cancer Register has showed that Māori women are diagnosed with more advanced disease, with 11% of Māori versus 4.6% of NZ European women having Stage IV disease at diagnosis (Seneviratne et al . ). This disparity was confirmed in a larger study of 12 385 women combining two NZ‐based breast cancer registers from Auckland and Waikato.…”
Section: Stage and Characteristics At Diagnosismentioning
confidence: 97%
“…In a study using a detailed clinical cancer registry including 2679 women with breast cancer, we found that compared to non‐Māori women, Māori women had a significantly higher age‐adjusted cancer‐specific mortality (HR 2.02, 95% CI 1.59–2.58) with significantly lower 5‐year (86.8% vs. 76.1%) and 10‐year (79.9% vs. 66.9%) crude cancer‐specific survivals (Seneviratne et al . ). Using the detailed data available on cancer biology, treatment and stage at diagnosis, we were able to explain almost all of the variation in mortality.…”
Section: Treatment and Survival Differencesmentioning
confidence: 97%
See 2 more Smart Citations